Wattpad User Satisfaction Analysis Using System Usability Scale (SUS) Method - Prita Dellia; Ayu Pratiwi; Nawafilillah; Tania Adela Sapitri; Annis Izzaturrahmah (Jurnal Riset Informatika, 2025)
Wattpad is an app that you can use to read, write, share, and comment on stories from various genres, such as romance, horror, fantasy, and more. This app is in high demand, especially by young people, because of its ease of use and provides many interesting stories for free. In this study, the author wants to find out how easy and convenient the Wattpad application is to be used by its users. For this reason, the System Usability Scale (SUS) method is used, which is a measurement tool commonly used to assess the usability of a system or application. Researchers collected data by distributing a questionnaire via Google Forms to 50 people who used Wattpad. The results of the questionnaire showed that the average SUS score obtained was 72.2. This value is included in the "C" category with the label "Good". This means that in general, Wattpad is considered quite good and comfortable to use. However, the results of the study also show that there are still some things that can be improved, such as feature clarity, fixes if the app crashes, and the number of ads that appear in the free version. If these shortcomings are addressed, then Wattpad can become even better and more fun for its users to use.